Thermodynamic transformation determining the essence of time - Dobija, Mieczysław; Renkas, Jurij (International Journal of Physical Research, 2023)
The consistent application of thermodynamic knowledge makes it possible to analyze in detail and modify the definition of time formulated by Isaac Newton. It also makes it possible to integrate Immanuel Kant's ideas about the relationship of human sensuality with the modern category of time. As a result of these analyses, there is an updated definition and indication of the constant that determines the rate of passage of time. A distinction between the concepts of time and duration emerged, making it possible to conclude that only processes described by the category of duration can be reversible. Other processes considered in terms of time are irreversible. The main purpose of this article is to precisely define the original thermodynamic transformation, which is the basis for measuring the pace and feeling of the course of time.